Efforts to improve speed in non-professional athletes: An application of plyometric training in badminton - Zulnadila Zulnadila (Khatulistwa Education Center, 2025)
Background Speed is one of the most important physical components in badminton as it determines an athlete’s ability to respond to attacks and return the shuttlecock to areas that are difficult for opponents to reach. Athletes with optimal speed can control the game’s tempo and increase their chances of winning. One effective method to improve speed is plyometric training, which utilizes explosive muscle contractions to optimize strength and power. Objectives This study aimed to examine the effect of plyometric training on improving the speed of non-professional badminton athletes. Methods A pre-experimental design with a one-group pretest–posttest approach was employed. The participants were 15 non-professional female athletes aged 20–25 years, all with normal blood pressure and resting heart rates. The training program consisted of box jump, box shuffle, and squat jump, conducted three times per week for six weeks (a total of 18 sessions). Speed was measured before and after the intervention using the 30-meter running test. Data were analyzed using a paired-sample t-test with a 5% significance level. Results The results showed a significant improvement in mean speed from 4.49 ± 0.17 seconds to 4.14 ± 0.21 seconds (p ≤ 0.001). It is concluded that a structured plyometric training program effectively increases the speed of non-professional badminton athletes. Conclusion The contribution of this study is to provide empirical evidence for coaches and athletes that plyometric training can be integrated into physical conditioning programs as a strategy to optimize on-court performance.